Separatism in Europe. Some aspects (International relations and international law Journal, 2016)
In the article it has being discussed some future aspects of the multinational states in Europe region. Trend for the regionalization process is becoming more explicit exactly as a form of self-identification of territorial communities within the nation-state in the European space. Examples of such situation’s development which had being presented in the article completely confirm the popularity of autonomist and even separatist tendencies on the continent: the situation in Belgium was being critical for a long time, but political crisis, which was caused by the desire for secession of the Flemish part of the population, had been overcome only recently; nothing is still clear in Catalonia, because of no legal force of positive results of a survey on the independence of the region. The future is still uncertain for the countries which are being tested for integrity, but it is possible to determine at least two points of view on the processes in these states: Euro-optimists consider Europe region development’s idea, erasing the borders between EU Member States as the solution of the present situation; Eurosceptics, oppositly, believe that it would exacerbate the national inequality.
Keywords: separatism; regionalism; autonomism; federalism; the three-tier structure; Flanders; Wallonia; Catalonia